Data on all levels is very valuable to the value chain - Laperrière, André (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Executive Director of the Secretariat for Global Open Data for Agriculture and Nutrition (GODAN) is André Laperrière. Here, he describes what GODAN have to do to raise awareness about the potential of agricultural data and how to get policymakers and donors on-board.